Experimental analysis of the correlation between bending strength and SMFL of corroded RC beams. (30th July 2019) - Qiu, Junli; Zhang, Hong; Zhou, Jianting; Ma, Hu; Liao, Leng
Highlights: A correlation between bending strength and SMFL of corroded RC beams was explored. A simplified theoretical model was established. An SMFL feature was used to estimate the bending strength of corroded RC beams. The experimental results agreed with those of the theoretical analysis. Abstract: Measuring the bearing capacity is critical for assessing the safety and durability of civil engineering structures. However, the existing non-destructive testing (NDT) techniques cannot estimate the bending strengths of corroded reinforced concrete (RC) beams easily. Thus, the correlation between self-magnetic flux leakage (SMFL) and bending strength of corroded RC beams was investigated in this study to estimate the bending strength. First, a theoretical model was established based on the physical properties of ferromagnetic materials and engineering mechanics. Preliminary research found that the peak-to-valley differences of the SMFL curves of corroded RC beams were strongly correlated with the bending strength. The normalized peak-to-valley differences NBP ( x ) and normalized bending strength NBS were defined based on this correlation. NBS of corroded RC beams can be evaluated using NBP ( x ) of SMFL curves. The data from 18 corroded RC beams and the theoretical model were analyzed and employed to verify the correlation between NBP ( x ) and NBS . The experimental results were consistent with those predicted by theory and showed the semi-quantitative correlation that NBP ( x ) was related to NBS exponentially (without stirrups) or approximate linearly (with stirrups). Therefore, the bending strength can be estimated semi-quantitatively via the SMFL curves. In this work, a novel correlation between the SMFL and bending strengths of corroded RC beams was established. The SMFL technique can be regarded as a new effective NDT technique for estimating the bending strength of corroded RC beams.